Positive electrode active material and method for producing same
By using water washing and heat treatment technology in the production process of positive electrode active materials, lithium chelate compounds and Li-MO solid solution coatings are formed, the lithium residue problem is solved, the process is simplified, and the battery performance is improved.
Patent Information
- Application Number
- JP2023511985
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-30
- Filing Date
- 2021-10-29
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-10-29
AI Technical Summary
In the prior art, when producing positive electrode active materials, it is difficult to effectively remove lithium compounds on the surface, resulting in a decrease in battery capacity and output power, and a large process step and high cost.
By using water washing method, the precursor of the positive electrode active material is mixed with a raw material with a high lithium content. After calcination, it is washed with a water washing solution containing chelating ions to form a surface coating of lithium chelate compounds, and a Li-MO solid solution coating is formed by heat treatment.
It effectively reduces the remaining lithium compounds on the surface, simplifies the process steps, improves the lithium ion conductivity and electrical conductivity of the battery, reduces the internal resistance, and improves the capacity and life of the battery.
Smart Images

Figure 0007670420000003 
Figure 0007670420000004 
Figure 0007670420000001
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0142916 filed on October 30, 2020, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference. The present invention relates to a positive electrode active material and a method for producing the same. [Background technology]
[0002] With the technological development and increasing demand for mobile devices, the demand for secondary batteries as an energy source is rapidly increasing. Among these secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.
[0003] Lithium transition metal composite oxides are used as the positive electrode active material for lithium secondary batteries. Among them, LiCoO has a high working voltage and excellent capacity characteristics. 2 The lithium-cobalt composite metal oxide LiCoO is mainly used. 2 However, due to the instability of the crystal structure caused by the delithiation, its thermal properties are very poor, and it is expensive, so there are limitations to its mass use as a power source in fields such as electric vehicles.
[0004] The LiCoO 2 As a replacement for lithium manganese mixed metal oxide (LiMnO 2 Or LiMn 2 O 4 etc.), lithium iron phosphate compounds (LiFePO 4 etc.) or lithium nickel composite metal oxide (LiNiO 2 Among them, lithium nickel composite metal oxides, which have a high reversible capacity of about 200 mAh / g and therefore can be used to easily realize large-capacity batteries, have been the subject of active research and development. However, the LiNiO 2 LiCoO 2In contrast, the thermal stability of lithium-ion batteries is inferior to that of lithium-ion batteries, and if an internal short circuit occurs due to external pressure while the battery is being charged, the positive electrode active material itself decomposes, causing the battery to explode or catch fire.
[0005] Therefore, LiNiO 2 As a method for improving the low thermal stability while maintaining the excellent reversible capacity of the lithium-ion battery, nickel-cobalt-manganese-based lithium composite transition metal oxides in which part of Ni is replaced with Mn and Co, and nickel-cobalt-aluminum-based lithium composite transition metal oxides in which part of Ni is replaced with Mn and Al have been developed.
[0006] The surface of the lithium composite transition metal oxide contains LiOH, Li 2 CO 3 In order to minimize such lithium by-products, the calcined product obtained by calcining the positive electrode active material precursor and the lithium-containing raw material was washed with water and then degassed with Al. 2 O 3 In the past, the battery was coated with inorganic oxides such as rubbing alcohol, but this method required two steps, a washing process and a coating process, which was costly. In addition, the use of inorganic oxide powder resulted in low coating uniformity, with a thick coating layer mainly formed only on the surface of the secondary particles. This made it difficult to achieve excellent lithium ion conductivity and electrical conductivity, and side reactions with the electrolyte were likely to occur, resulting in reduced battery capacity, output, and lifespan.
[0007] Therefore, there is a need for a method for manufacturing a positive electrode active material that can minimize residual lithium that may remain on the surface of the positive electrode active material, can provide a uniform and thin coating on the surfaces of primary particles of the positive electrode active material, and suppresses side reactions with the electrolyte, thereby providing excellent capacity and life characteristics. Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention provides a method for manufacturing a positive electrode active material, which can minimize residual lithium that may remain on the surface of the positive electrode active material, reduce process steps, and solve the problem of reduced capacity and output of a battery, and a positive electrode active material manufactured thereby. [Means for solving the problem]
[0009] The present invention provides a method for producing a positive electrode active material, the method comprising the steps of: a first step of mixing a positive electrode active material precursor, which is a transition metal hydroxide or a transition metal oxyhydroxide, and a lithium-containing raw material, followed by calcining to produce a calcined product; a second step of washing the calcined product with an aqueous washing solution containing a coating layer precursor containing a chelate anion, followed by drying to produce a lithium transition metal oxide having a coating layer containing a lithium chelate compound formed thereon; and a third step of heat-treating the lithium transition metal oxide having a coating layer containing a lithium chelate compound formed thereon, to produce a lithium transition metal oxide having a coating layer containing a Li-M-O solid solution (wherein M is one or more elements selected from Nb, Co, Ti, V, Zr, Si, Al, and Mo), wherein the chelate anion contains one or more metals selected from Nb, Co, Ti, V, Zr, Si, Al, and Mo, and one or more ligands selected from oxalate, nitrite, carboxylate, borate, phosphate, and acetate.
[0010] The present invention also provides a positive electrode active material comprising a lithium transition metal oxide including secondary particles formed by aggregation of primary particles, the primary particles having a coating layer formed on the surface thereof, the coating layer including a Li-M-O solid solution (M is one or more elements selected from Ti, V, Co, Zr, Nb, Si, Al, and Mo). Effect of the Invention
[0011] The present invention uses a washing solution containing a coating layer precursor including a chelate anion that selectively reacts with lithium by-products remaining on the surface of the positive electrode active material, thereby minimizing lithium by-products that may remain on the surface of the positive electrode active material.
[0012] In addition, the washing step and the coating step can be carried out simultaneously using the washing solution, thereby reducing the number of process steps.
[0013] In addition, the coating layer formed from the coating layer precursor has excellent lithium ion conductivity and electrical conductivity, and as a result, there is an advantage that a lithium secondary battery having a small internal resistance can be realized. [Brief description of the drawings]
[0014] [Figure 1] 1 is a SEM image of a positive electrode active material 1 prepared in Example 1. [Diagram 2] 1 shows TEM-EDS mapping data of a positive electrode active material 1 prepared in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0016] In this specification, the terms "including," "comprising," or "having" are intended to specify the presence of embodied features, numerals, steps, components, or combinations thereof, but are not intended to preclude the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.
[0017] In this specification, the term "primary particle" refers to the smallest particle unit that can be recognized when observing a positive electrode active material particle through a scanning electron microscope, and the term "secondary particle" refers to a secondary structure formed by aggregation of a plurality of primary particles.
[0018] The present invention will now be described in more detail.
[0019] Method for producing positive electrode active material The present inventors have found that when a washing solution containing a coating layer precursor including a chelate anion that selectively reacts with lithium by-products remaining on a fired product during a washing process is used in the preparation of a lithium transition metal oxide, it is possible to minimize lithium by-products that may remain on the surface of a positive electrode active material and form a coating layer having excellent lithium ion conductivity and electrical conductivity, and have completed the present invention.
[0020] The method for producing a positive electrode active material according to the present invention includes a first step of mixing a positive electrode active material precursor, which is a transition metal hydroxide or a transition metal oxyhydroxide, and a lithium-containing raw material, followed by calcining the mixture to produce a calcined product; a second step of washing the calcined product with an aqueous washing solution containing a coating layer precursor containing a chelate anion, followed by drying to produce a lithium transition metal oxide having a coating layer containing a lithium chelate compound formed thereon; and a third step of heat-treating the lithium transition metal oxide having a coating layer containing a lithium chelate compound formed thereon to produce a lithium transition metal oxide having a coating layer containing a Li-M-O solid solution (wherein M is one or more elements selected from Nb, Co, Ti, V, Zr, Si, Al, and Mo), wherein the chelate anion contains one or more metals selected from Nb, Co, Ti, V, Zr, Si, Al, and Mo, and one or more ligands selected from oxalate, nitrite, carboxylate, borate, phosphate, and acetate.
[0021] In this specification, the metal, which is one or more metals selected from Nb, Co, Ti, V, Zr, Si, Al and Mo, means all transition metals, metalloids and other metals.
[0022] Each step of the method for producing a positive electrode active material will be specifically described below.
[0023] First Step The first step is a step of mixing a positive electrode active material precursor, which is a transition metal hydroxide or transition metal oxyhydroxide, and a lithium-containing raw material, and then calcining the mixture to produce a calcined product.
[0024] The positive electrode active material precursor may include secondary particles formed by aggregation of primary particles, and may have a composition represented by the following Chemical Formula 1 or 2:
[0025] [Chemical formula 1] [Ni a Co b M 1 c M 2 d ](OH) 2
[0026] [Chemical formula 2] [Ni a Co b M 1 c M 2 d ]O·OH
[0027] In the above Chemical Formula 1 and Chemical Formula 2, Said M 1 is one or more elements selected from Mn and Al, Said M 2 is one or more elements selected from B, Mg, Ca, Si, Ti, V, Cr, Fe, Zn, Ga, Y, Zr, Nb, Mo, Ta and W, 0.6≦a<1, 0 <b≦0.4、0<c≦0.4、0≦d≦0.1、a+b+c+d=1である。
[0028] The a means the atomic fraction of nickel among the metal elements in the precursor, and may be 0.6≦a<1, 0.6≦a≦0.98, or 0.7≦a≦0.95.
[0029] The b represents the atomic fraction of cobalt among the metal elements in the precursor, and is 0 <b≦0.4、0.01≦b≦0.4または0.01≦b≦0.3であることができる。
[0030] The c is the metal element M in the precursor. 1 means the atomic fraction of an element, 0 <c≦0.4、0.01≦c≦0.4または0.01≦c≦0.3であることができる。
[0031] The d is the number of metal elements in the precursor, M 2 It means the atomic fraction of an element and can be 0≦d≦0.1 or 0≦d≦0.05.
[0032] The lithium-containing raw material may include at least one selected from the group consisting of lithium hydroxide hydrate, lithium carbonate, and lithium hydroxide. The lithium-containing raw material may be, for example, lithium hydroxide hydrate, more specifically, LiOH·H 2 In this case, the reactivity of the precursor having a high atomic fraction of nickel among the metal elements in the precursor with the lithium-containing raw material can be improved.
[0033] The positive electrode active material precursor and the lithium-containing raw material may be mixed in a molar ratio of 1:1.0 to 1:1.10, specifically 1:1.03 to 1:1.08, more specifically 1:1.05 to 1:1.07. When the lithium-containing raw material is within the above range, the capacity reduction of the positive electrode active material can be prevented.
[0034] The first step of firing can be carried out at 700° C. to 950° C. The firing temperature can be specifically 750° C. to 850° C., more specifically 750° C. to 800° C. When the firing temperature is within the above range, crystals can be formed to an appropriate size, and process costs can be reduced.
[0035] The first step of firing can be carried out in an oxygen atmosphere, in which case a fired product having a structurally stable phase can be formed.
[0036] The first step of firing can be performed for 5 to 24 hours. Specifically, the firing can be performed for 5 to 12 hours, and more specifically, for 5 to 10 hours. When the firing time is within the above range, firing can be performed smoothly without deviation (uniformly) at each firing position.
[0037] Second step The second step is a step of washing the fired product with a washing solution containing a coating layer precursor containing a chelate anion, and then drying the fired product to produce a lithium transition metal oxide having a coating layer containing a lithium chelate compound.
[0038] The chelating anion contained in the coating layer precursor includes one or more metals selected from Ti, V, Co, Zr, Nb, Si, Al, and Mo, and one or more ligands selected from oxalate, nitrite, carboxylate, borate, phosphate, and acetate.
[0039] The second step is to remove lithium by-products, which are impurities present in the fired product, particularly Li 2 CO 3 and forming a coating layer containing a lithium chelate compound. The present invention can reduce the number of process steps by simultaneously performing the washing step and the coating step using the washing solution.
[0040] The chelate anion contained in the coating layer precursor specifically includes one or more transition metals selected from Nb, Co, and Ti and one or more ligands selected from oxalate and nitrite. The chelate anion is more specifically [NbO(C 2 O 4 ) 2 ] - , [Co(NO 2 ) 6 ] 3- and [TiO(C 2 O4 ) 2 ] - In this case, the reactivity of the chelate anion with lithium by-products is high, so that impurities can be easily removed, and the coating layer precursor containing the chelate anion is easily dissolved in a solvent of a washing solution, so that a coating layer containing a lithium chelate compound even in the primary particles of a lithium transition metal oxide can be formed.
[0041] The coating layer containing the lithium chelate compound may be a compound formed by reacting a lithium by-product with a coating layer precursor containing the chelate anion. For example, Li 2 CO 3 The coating layer precursor containing the chelate anion reacts with the lithium ion through an acid-base reaction, and the lithium ion and the chelate anion are combined to form a lithium chelate compound (e.g., LiNbO(C 2 O 4 ) 2 , Li 3 Co(NO 2 ) 6 , LiTiO(C 2 O 4 ) 2 ) can be formed. As a result, the lithium by-products remaining on the surface of the positive electrode active material can be minimized by performing a water washing process using a water washing solution containing a coating layer precursor containing a chelate anion, which is an anion inorganic salt that selectively reacts with the lithium by-products remaining in the fired product in the second step. Meanwhile, the coating layer containing the lithium chelate compound becomes a coating layer containing a Li-M-O solid solution (M is at least one selected from Ti, V, Co, Zr, Nb, Si, Al, and Mo), which is a coating layer with excellent lithium ion conductivity and electrical conductivity, through a third step described below.
[0042] The coating layer precursor is an ammonium salt (NH 4 + ), sodium salt (Na + ), potassium salt (K + ), hydrogen cation (H +) and lithium salts (Li + That is, the coating layer precursor may include the chelate anion and the cation.
[0043] The coating layer precursor may be one or more selected from ammonium niobium oxalate, sodium cobalt nitrite, ammonium titanium oxalate, and sodium titanium oxalate. In this case, the effect of removing residual lithium can be achieved simultaneously with the formation of an inorganic oxide coating layer.
[0044] The second step of washing with water can be performed by adding the washing solution in an amount of 50 to 300 parts by weight, specifically 100 to 200 parts by weight, and more specifically 100 to 150 parts by weight, based on 100 parts by weight of the sintered product. When the content of the washing solution is within the above range, the sintered product does not gel, and lithium in the sintered product structure does not dissolve.
[0045] The coating layer precursor contained in the washing solution may be included in an amount of 0.1 to 5 parts by weight based on 100 parts by weight of the sintered product. The coating layer precursor may be included in an amount of, specifically, 0.1 to 2 parts by weight, more specifically, 0.2 to 1.8 parts by weight based on 100 parts by weight of the sintered product. In this case, lithium by-products that may remain on the surface of the positive electrode active material may be minimized, and a coating layer containing the lithium chelate compound may be appropriately formed.
[0046] The solvent of the washing solution may be one or more selected from deionized water, distilled water, and ethanol. Specifically, the solvent of the washing solution may be deionized water and / or distilled water. In this case, the solubility of the coating layer precursor containing the chelate anion may increase, and thus the reactivity of the lithium by-product and the chelate anion may increase, so that the coating layer containing the lithium chelate compound may be easily formed. Specifically, when the fired product contains secondary particles formed by agglomeration of primary particles, the washing solution in which the coating layer precursor is dissolved in large amounts may penetrate to the surfaces of the primary particles, and as a result, a coating layer containing a Li-M-O solid solution (M is one or more selected from Ti, V, Co, Zr, Nb, Si, Al, and Mo) may be formed on the surfaces of the primary particles.
[0047] The solvent of the washing solution may be included in an amount of 50 to 200 parts by weight, based on 100 parts by weight of the sintered product. The coating layer precursor may be included in an amount of, specifically, 50 to 150 parts by weight, more specifically, 70 to 150 parts by weight, based on 100 parts by weight of the sintered product. In this case, impurities may be sufficiently washed away, and lithium present inside the sintered product may not leak, preventing a decrease in battery performance.
[0048] The second step of washing with water can be carried out at 5° C. to 70° C. When the temperature for carrying out the washing process is within the above range, the process cost can be reduced.
[0049] The second step of washing with water can be performed for 10 to 60 minutes. When the washing process is performed for a time within this range, the coating layer containing the lithium chelate compound is easily formed, and lithium present inside the oxide does not leak during washing with water, so that the battery performance does not deteriorate.
[0050] The drying is for removing moisture from the lithium transition metal oxide that has been subjected to the water washing process, and can be carried out at 60° C. to 150° C. after removing moisture using a vacuum pump. Specifically, the drying can be carried out for 12 hours or more under a temperature condition of 60° C. to 150° C.
[0051] Third step The third step is a step of heat-treating the lithium transition metal oxide having a coating layer containing the lithium chelate compound formed thereon, to produce a lithium transition metal oxide having a coating layer containing a Li-M-O solid solution (wherein M is one or more elements selected from Ti, V, Co, Zr, Nb, Si, Al, and Mo).
[0052] The second step is to heat-treat the lithium chelate compound (e.g., LiNbO(C 2 O 4 ) 2 , Li 3 Co(NO 2 ) 6 , LiTiO(C 2 O 4 ) 2 When heat is applied to the lithium transition metal oxide on which the coating layer containing the lithium chelate compound is formed, carbon, nitrogen, etc. contained in the lithium chelate compound are converted into CO, CO 2 , NO 2 etc., and is removed in a gaseous state to form a Li-M-O solid solution having excellent lithium ion conductivity and electrical conductivity. That is, when the coating layer containing the lithium chelate compound undergoes the third step, it becomes a coating layer containing a Li-M-O solid solution (M is one or more selected from Ti, V, Co, Zr, Nb, Si, Al, and Mo), which is a coating layer having excellent lithium ion conductivity and electrical conductivity.
[0053] The coating layer containing the Li-M-O solid solution may have a thickness of 1 nm to 50 nm, specifically 2 nm to 50 nm, more specifically 5 nm to 10 nm. In this case, the performance of the positive electrode active material is not deteriorated, and the capacity characteristic and internal resistance characteristic of the battery at high temperatures can be improved.
[0054] The heat treatment can be performed at 500°C to 900°C, specifically 500°C to 800°C, and more specifically 500°C to 700°C. If the heat treatment temperature is less than 500°C, carbon, nitrogen, etc. contained in the lithium chelate compound may be difficult to remove, and if the heat treatment temperature exceeds 900°C, lithium inside the lithium transition metal oxide may leak, resulting in a decrease in capacity. If the heat treatment temperature is within the above range, a coating layer can be formed while maintaining the structural stability of the lithium transition metal oxide.
[0055] The heat treatment can be performed under an oxygen atmosphere, a nitrogen atmosphere, or an air atmosphere. Specifically, the heat treatment can be performed under an oxygen atmosphere. In this case, carbon, nitrogen, etc. contained in the lithium chelate compound can be easily removed, and a uniform oxide coating layer can be formed.
[0056] The heat treatment can be performed for 5 to 24 hours. When the heat treatment time is within the above range, a proper coating layer can be formed and production efficiency can be improved.
[0057] positive electrode active material The positive electrode active material according to the present invention comprises a lithium transition metal oxide including secondary particles formed by aggregation of primary particles, and the primary particles have a coating layer formed on the surface thereof, the coating layer including a Li-M-O solid solution (M is one or more elements selected from Ti, V, Co, Zr, Nb, Si, Al, and Mo).
[0058] The positive electrode active material according to the present invention may be produced according to the method for producing the positive electrode active material.
[0059] The Li-MO solid solution may contain one or more selected from Li-Nb-O, Li-Co-O, and Li-Ti-O. Specifically, the Li-MO solid solution may be LiNbO 2 , LiNbO 3 , LiCoO 2 and Li 2 TiO 3 More specifically, LiNbO 3 and LiCoO 2 In this case, the coating layer containing the Li-M-O solid solution has excellent lithium ion conductivity and electrical conductivity, and as a result, a lithium secondary battery having low internal resistance can be realized.
[0060] The coating layer containing the Li-M-O solid solution may have a thickness of 1 nm to 50 nm, specifically 2 nm to 50 nm, more specifically 5 nm to 10 nm, which does not deteriorate the performance of the positive electrode active material and can improve the capacity characteristics and internal resistance characteristics of the battery at high temperatures.
[0061] The lithium transition metal oxide may have a composition represented by the following Formula 3.
[0062] [Chemical formula 3] Li e [Ni a’ Co b’ M 1 c’ M 2 d’ ]O 2-f A f
[0063] In the above Chemical Formula 3, Said M 1 is one or more elements selected from Mn and Al, Said M 2 is one or more elements selected from B, Mg, Ca, Si, Ti, V, Cr, Fe, Zn, Ga, Y, Zr, Nb, Mo, Ta and W, A is one or more elements selected from F, Cl, Br, I, At, S and Se, 0.9≦e≦1.1, 0.6≦a'<1, 0 <b’≦0.4、0<c’≦0.4、0≦d’≦0.1、a’+b’+c’+d’=1、0≦f≦0.2である。
[0064] The a' means the atomic fraction of nickel among metal elements other than lithium in the positive electrode active material, and may be 0.6≦a'<1, 0.6≦a'≦0.98, or 0.7≦a'≦0.95.
[0065] The b' means the atomic fraction of cobalt among the metal elements other than lithium in the positive electrode active material, and is 0 <b’≦0.4、0.01≦b’≦0.4または0.01≦b’≦0.3であることができる。
[0066] The c' is M among the metal elements other than lithium in the positive electrode active material. 1 means the atomic fraction of an element, 0 <c’≦0.4、0.01≦c’≦0.4または0.01≦c’≦0.3であることができる。
[0067] The d' is the M of the metal elements other than lithium in the positive electrode active material. 2 It means the atomic fraction of an element and can be 0≦d'≦0.1 or 0≦d'≦0.05.
[0068] positive electrode The present invention also provides a positive electrode for a lithium secondary battery, which contains the positive electrode active material produced by the above-mentioned method.
[0069] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector and including the positive electrode active material.
[0070] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0071] The positive electrode active material layer may contain a conductive material and a binder in addition to the positive electrode active material.
[0072] The positive electrode active material may be included in an amount of 80 wt% to 99 wt%, more specifically, 85 wt% to 98 wt%, based on the total weight of the positive electrode active material layer. When included in the above range, excellent capacity characteristics can be exhibited.
[0073] The conductive material is used to give conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and among these, one type alone or a mixture of two or more types can be used. The conductive material can be contained in an amount of 1% by weight to 30% by weight based on the total weight of the positive electrode active material layer.
[0074] The binder serves to improve adhesion between the positive electrode active material particles and adhesion between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 wt% to 30 wt% based on the total weight of the positive electrode active material layer.
[0075] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by applying a composition for forming a positive electrode active material layer, which is prepared by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent, onto a positive electrode current collector, followed by drying and rolling. In this case, the types and contents of the positive electrode active material, binder, and conductive material are as described above.
[0076] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and may be used alone or in combination of two or more of these. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity during subsequent coating for the manufacture of a positive electrode, taking into consideration the coating thickness of the slurry and the manufacturing yield.
[0077] As another method, the positive electrode can also be produced by casting the composition for forming a positive electrode active material layer on another support, peeling the composition from the support, and laminating the resulting film on a positive electrode current collector.
[0078] Lithium secondary battery In addition, the present invention can provide an electrochemical device including the positive electrode. The electrochemical device can be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.
[0079] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Since the positive electrode is as described above, a detailed description thereof will be omitted, and only the remaining components will be described in detail below.
[0080] Also, the lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.
[0081] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0082] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0083] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material.
[0084] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), SnO 2 Examples of the negative electrode active material include metal oxides capable of doping and dedoping lithium, such as vanadium oxide and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, and any one or a mixture of two or more of these may be used. Also, a thin film of metallic lithium may be used as the negative electrode active material. Also, the carbon material may be either low crystalline carbon or high crystalline carbon. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.
[0085] The negative electrode active material may be included in an amount of 80% by weight to 99% by weight based on the total weight of the negative electrode active material layer.
[0086] The binder is a component that facilitates bonding between the conductive material, the active material, and the current collector, and may be added in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.
[0087] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, specifically 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of such conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0088] The negative electrode active material layer can be produced by applying a negative electrode mixture, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent, onto a negative electrode current collector and drying the applied mixture. Alternatively, the negative electrode mixture can be cast onto a separate support, and then peeled off from the support to obtain a film, which can be laminated onto the negative electrode current collector.
[0089] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent electrolyte moisture-absorbing ability is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, etc. can be used. In addition, a coated separator containing a ceramic component or a polymeric material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a single layer or multilayer structure.
[0090] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.
[0091] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0092] The organic solvent may be any solvent that can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Carbonate-based solvents such as ethylene carbonate (PC); alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes may be used. Among them, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can enhance the charge / discharge performance of the battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the cyclic carbonate and the linear carbonate are mixed in a volume ratio of about 1:1 to about 1:9, so that the electrolyte can exhibit excellent performance.
[0093] The lithium salt can be used without any particular limitation as long as it is a compound that can provide lithium ions used in a lithium secondary battery. 6 , LiClO 4 , LiAsF 6 , LiBF 4 , LiSbF 6 , LiAl0 4 , LiAlCl 4 , LiCF 3 SO 3 , LiC 4 F 9 SO 3 , LiN(C 2 F 5 SO 3 ) 2 , LiN(C 2 F 5 SO 2 ) 2 , LiN(CF 3 SO 2 ) 2 , LiCl, LiI, or LiB(C 2 O 4 ) 2 etc. can be used. The lithium salt is preferably used in a concentration range of 0.1 M to 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore can exhibit excellent electrolyte performance and can effectively move lithium ions.
[0094] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, in order to improve the life characteristics of the battery, suppress the decrease in the capacity of the battery, and improve the discharge capacity of the battery. In this case, the additives may be contained in an amount of 0.1% by weight to 5% by weight based on the total weight of the electrolyte.
[0095] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and capacity retention rate, and is therefore useful in portable devices such as mobile phones, notebook computers and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).
[0096] Therefore, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.
[0097] The battery module or battery pack may be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.
[0098] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0099] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but also as a unit battery for a medium- to large-sized battery module including a large number of battery cells.
[0100] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein.
[0101] Examples and Comparative Examples Ni 0.88 Co 0.05 Mn 0.07 (OH) 2 A positive electrode active material precursor having a composition represented by the following formula was prepared.
[0102] LiOH·H as a lithium-containing raw material 2 O, the positive electrode active material precursor and LiOH H 2 The amount of HCl was adjusted so that the molar ratio of HCl to O was 1:1.07.
[0103] Example 1 The positive electrode active material precursor and the LiOH H 2 After mixing with O, the mixture was fired at 780° C. for 10 hours in an oxygen atmosphere with an oxygen concentration of 100% by volume to produce a fired product.
[0104] A wash solution was prepared by dissolving 0.49 parts by weight of ammonium niobium oxalate in 130 parts by weight of distilled water.
[0105] 130 parts by weight of the washing solution was added to 100 parts by weight of the fired product, mixed, and the fired product was washed with water for 5 minutes, filtered for 2 minutes using a vacuum pump, and dried in a vacuum oven at 130° C. for 24 hours to obtain lithium niobium oxalate (LiNbO(C 2 O 4 ) 2 ) containing a coating layer formed on LiNi0.88 Co 0.05 Mn 0.07 O 2 (hereinafter, A) was manufactured.
[0106] The above A was heat-treated at 600°C for 10 hours in an oxygen atmosphere with an oxygen concentration of 100% by volume to form a coating layer containing Li-Nb-O solid solution (LiNbO 3 (including compounds represented by the formula: 0.88 Co 0.05 Mn 0.07 O 2 (Positive electrode active material 1) was produced.
[0107] Example 2 Lithium niobium oxalate (LiNbO(C)) was prepared by dissolving 0.98 parts by weight of ammonium niobium oxalate in 130 parts by weight of distilled water. 2 O 4 ) 2 ) containing a coating layer formed on LiNi 0.88 Co 0.05 Mn 0.07 O 2 A positive electrode active material 2 was produced in the same manner as in Example 1, except that (hereinafter, B) was produced.
[0108] Example 3 Lithium cobalt nitrite (Li 3 Co(NO 2 ) 6 ) containing a coating layer formed on LiNi 0.88 Co 0.05 Mn 0.07 O 2 A positive electrode active material 3 was produced in the same manner as in Example 1, except that (hereinafter, C) was produced.
[0109] Comparative Example 1 The positive electrode active material precursor and the LiOH H 2 After mixing with O, the mixture was fired at 780° C. for 10 hours in an oxygen atmosphere with an oxygen concentration of 100% by volume to produce a fired product.
[0110] The calcined product was mixed with distilled water in a weight ratio of 1:1.3, and the calcined product was washed with water for 5 minutes, filtered for 2 minutes using a vacuum pump, and dried in a vacuum oven at 130° C. for 24 hours to obtain LiNi 0.88 Co 0.05 Mn 0.07 O 2 (Positive electrode active material 4) was produced.
[0111] Experimental Example Experimental Example 1: Structural analysis of positive electrode active material An image of the positive electrode active material 1 was obtained using a SEM device (QUANTA, FEG 256), and is shown in FIG.
[0112] TEM-EDS mapping data of the positive electrode active material 1 was obtained using a TEM device (FEI Titan G2 80-200 ChemiSTEM), and is shown in FIG.
[0113] 1 and 2, it can be seen that the positive electrode active material 1 includes secondary particles formed by aggregation of primary particles, and that the surfaces of the primary particles are uniformly coated with a Li-Nb-O solid solution.
[0114] Experimental Example 2: Evaluation of the amount of residual lithium remaining in the lithium transition metal oxide after washing with water and the amount of residual lithium remaining in the produced positive electrode active material 5 g of each of the positive electrode active materials A of Example 1, B of Example 2, C of Example 3, and Comparative Example 1 was added to 100 g of distilled water, mixed for 5 minutes, and then filtered. After filtering, the amount of Li dissolved in the distilled water was measured by titration using a pH meter. 2 CO 3 and the amount of LiOH was measured and is shown in Table 1.
[0115] [Table 1]
[0116] Referring to Table 1, it can be seen that in the cases of A, B, and C formed by washing the washed product with a washing solution in which ammonium niobium oxalate or sodium cobalt nitrite was dissolved, the amount of residual lithium, particularly the amount of lithium carbonate, is significantly less than that of the positive electrode active material 5. This is because the niobium oxalate anions or cobalt nitrite anions react with the residual lithium ions present in the washed product to form a coating layer containing lithium niobium oxalate or lithium cobalt nitrite.
[0117] For reference, the amount of lithium hydroxide in the positive electrode active material 4 is less than that in the examples because the solubility of LiOH is higher in the water used as the washing solution in Comparative Example 1.
[0118] Experimental example 3: Characterization of half-cells Lithium secondary batteries were produced using the positive electrode active materials produced in Examples 1 to 3 and Comparative Example 1, and the initial charge capacity, initial discharge capacity, capacity retention rate, and internal resistance of each of the lithium secondary batteries were evaluated.
[0119] Specifically, the positive electrode active materials prepared in Examples 1 to 3 and Comparative Example 1 were mixed with a carbon black conductive material and a PVDF binder in a weight ratio of 97.5:1.0:1.5 in NMP solvent to prepare positive electrode slurries. The positive electrode slurries were applied to one side of an aluminum current collector, dried at 130°C, and rolled to prepare positive electrodes. Meanwhile, Li metal disks were used as negative electrode active materials. An electrode assembly was prepared by interposing a separator between the positive and negative electrodes prepared as above, and the assembly was placed inside a battery case, and an electrolyte was injected into the case to prepare a lithium secondary battery. In this case, 1M LiPF in an EC / EMC / DEC (3 / 3 / 4, vol%) organic solvent was used as the electrolyte. 6 An electrolyte solution in which the above was dissolved was injected into the battery to prepare a lithium secondary battery.
[0120] The lithium secondary battery prepared as above was charged at 25° C. at a constant current of 0.1 C until the voltage reached 4.25 V, and then discharged at a constant current of 0.1 C until the voltage reached 3.0 V. The initial charge capacity and initial discharge capacity are shown in Table 2. Also, the DCIR value calculated by dividing the voltage by the current after 60 seconds in the initial discharge cycle is shown in Table 2.
[0121] Then, charge / discharge cycles were repeated 20 times at 45° C., in the range of 3.0 to 4.25 V, at a constant current of 0.33 C, and the capacity of the lithium secondary battery was measured, and in particular, the ratio of the 20th cycle capacity to the 1st cycle capacity was taken as the capacity retention rate, which is shown in the following Table 2. In addition, the ratio of DCIR determined in the 20th discharge cycle to DCIR determined in the 1st discharge cycle was taken as the resistance increase rate, which is shown in the following Table 2.
[0122] [Table 2]
[0123] Referring to Table 2, it can be seen that the batteries including the positive electrode active materials of Examples 1 to 3 have comparable initial charge capacity and initial discharge capacity, excellent capacity retention at high temperatures, and low internal resistance compared to the battery including the positive electrode active material of Comparative Example 1. This is because the amount of residual lithium remaining in the positive electrode active material is small, and the positive electrode active material includes a coating layer including a Li-M-O solid solution having high lithium ion conductivity.
Claims
1. a first step of mixing a positive electrode active material precursor, which is a transition metal hydroxide or a transition metal oxyhydroxide, and a lithium-containing raw material, and then calcining the mixture to produce a calcined product; a second step of washing the fired product with a washing solution containing a coating layer precursor containing a chelate anion, and then drying the fired product to produce a lithium transition metal oxide having a coating layer containing a lithium chelate compound formed thereon; and a third step of heat-treating the lithium transition metal oxide having the coating layer including the lithium chelate compound formed thereon to produce a lithium transition metal oxide having a coating layer including a Li-M-O solid solution (wherein M is one or more elements selected from Nb, Co, Ti, V, Zr, Si, Al, and Mo). the chelating anion comprises one or more metals selected from Nb, Co, Ti, V, Zr, Si, Al and Mo, and one or more ligands selected from oxalate, nitrite, carboxylate, borate, phosphate and acetate; The method for producing a positive electrode active material, wherein the first step of baking is carried out for 5 to 12 hours.
2. The positive electrode active material precursor has a composition represented by the following Chemical Formula 1 or the following Chemical Formula 2: [Chemical formula 1] [Ni a Co b M 1 c M 2 d ](O+) 2 [Chemical formula 2] [Ni a Co b M 1 c M 2 d ]O・OH In the above Chemical Formula 1 and Chemical Formula 2, Said M 1 is one or more elements selected from Mn and Al, Said M 2 is one or more elements selected from B, Mg, Ca, Si, Ti, V, Cr, Fe, Zn, Ga, Y, Zr, Nb, Mo, Ta and W; The method for producing a positive electrode active material according to claim 1 , wherein 0.6≦a<1, 0<b≦0.4, 0<c≦0.4, 0≦d≦0.1, and a+b+c+d=1.
3. 3. The method for producing a positive electrode active material according to claim 1, wherein the positive electrode active material precursor and the lithium-containing raw material are mixed in a molar ratio of 1:1.0 to 1:1.
10.
4. The method for producing a positive electrode active material according to any one of claims 1 to 3, wherein the firing is carried out at a temperature of 700°C to 950°C.
5. 5. The method for producing a positive electrode active material according to claim 1, wherein the chelate anion is one or more transition metals selected from Nb, Co, and Ti and one or more ligands selected from oxalate and nitrite.
6. The coating layer precursor is an ammonium salt (NH 4 + ), sodium salt (Na + ), potassium salt (K + ), hydrogen cation (H + ) and lithium salt (Li + The method for producing a positive electrode active material according to claim 1 , further comprising:
7. The method for producing a positive electrode active material according to claim 1 , wherein the coating layer precursor is at least one selected from the group consisting of ammonium niobium oxalate, sodium cobalt nitrite, ammonium titanium oxalate, and sodium titanium oxalate.
8. The method for producing a positive electrode active material according to any one of claims 1 to 7, wherein the coating layer precursor contained in the washing solution is contained in an amount of 0.1 to 5 parts by weight based on 100 parts by weight of the fired product.
9. 9. The method for producing a positive electrode active material according to claim 1, wherein the washing with water is performed by adding 50 parts by weight to 300 parts by weight of the washing solution with respect to 100 parts by weight of the fired product.
10. The method for producing a positive electrode active material according to any one of claims 1 to 9, wherein the heat treatment is carried out at 500°C to 900°C.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery, method for manufacturing the same and lithium secondary battery
JP2012113823A
Lithium ion secondary battery and method of manufacturing cathode active material for lithium ion secondary battery
JP2013137947A
Solution containing lithium and niobium complex, method for producing the same, and lithium ion battery
JP2015103321A
Composite cathode active material, method of preparing the same, and cathode and lithium battery including the composite cathode active material
JP2019046795A
Positive electrode active material for lithium ion secondary battery and method for producing the same, positive electrode mixture paste for lithium ion secondary battery, and lithium ion secondary battery
JP2020053383A